CLinical EValuation of WEB 17 device in intracranial aneuRysms (CLEVER): 1-year effectiveness results for ruptured and unruptured aneurysms - Spelle, Laurent; Costalat, Vincent; Caroff, Jildaz; Wodarg, Fritz; Fischer, Sebastian; Herbreteau, Denis; Möhlenbruch, Markus Alfred; Januel, Anne-Christine; Papagiannaki, Chrysanthi; Klisch, Joachim; Numminen, Jussi; Rautio, Riitta; et al. (Journal of neuroInterventional surgery, 2024)
Background The Woven EndoBridge (WEB) device is designed to treat wide-necked bifurcation aneurysms. The WEB 17 is the latest iteration and can be delivered through a 0.017″ microcatheter. The CLEVER study demonstrated that WEB 17 is safe and effective for providing protection against bleeding or rebleeding at 1 month and 1 year. - Objective To evaluate angiographic stability at 1 year. - Methods The CLEVER study was a prospective multicenter study conducted in 17 European centers, involved 163 subjects, comprising 60 ruptured and 103 unruptured aneurysms. Independent assessment of 1-year follow-up imaging was incorporated into the study design. - Results Aneurysm diameters ranged from 2.0 to 9.2 mm, with 95.7% being broad-based (dome-to-neck ratio <2). Follow-up imaging at 1 year was completed for 146 out of 163 subjects (89.6%) and evaluated by an independent core laboratory. The primary efficacy endpoint of adequate occlusion without re-treatment at 1 year was achieved for 120 (82.2%) of all subjects. At 1 year, the adequate occlusion rate was 86.5% for ruptured aneurysms (73.1% complete occlusion) and 82.4% for unruptured aneurysms (57.1% complete occlusion). The overall re-treatment rate at 1 year was 2.6% (4/152), with 3.1% (3/97) for unruptured aneurysms and 1.8% (1/55) for ruptured aneurysms - Conclusion Delivery of the WEB 17 via 0.017 inch catheters represents a significant evolution of the WEB design. The results of CLEVER presented here demonstrate that it maintains the same efficacy as previous generations of WEB.
Zuerst online veröffentlicht: 11. Juli 2024
Gesehen am 17.02.2025